Orientación profesional y aptitudes e intereses de los estudiantes del tercer año de bachillerato de la Unidad Educativa Fiscomisional “La Dolorosa”. - Loján Guzmán, Ana Cristina (2023)
Professional orientation represents a structured professional guidance process wherein individuals employ psychoanalytic methodologies to explore their inner selves uncovering their interests, abilities, and aptitudes. This process involves acquiring pertinent and current information for a well-informed decision-making process concerning a career path that aligns with their individual needs and maximizes personal satisfaction. The absence of tailored guiding framework adapted to the evolving demands of contemporary social and professional landscapes has resulted in elevated levels of personal discontent among professionals, a rise in university drop-out rates among students, and a scarcity of individuals pursuing professions driven by genuine vocational passion within our society. The aim of this study is to analyze the aptitudes and interests as integral components of the professional orientation process in selecting a university major, and to design a comprehensive professional orientation program aimed at facilitating informed decision-making. To accomplish this objective, the CHASIDE professional orientation test was applied to a cohort of 31 third-year high school students enrolled in the evening section at the Fiscomisional Educational Unit "La Dolorosa". Based on the conducted analysis, it was identified that the surveyed population consists of adult learners currently pursuing secondary education. The predominant field of interest among them was identified as Defense and Security, although this did not necessarily align with their respective abilities. In contrast, the field of Administrative Science presented a higher degree of alignment between interests and aptitudes, while all other professional fields presented varying degrees of vocational conflict. When segmenting the data by gender, it became evident that higher rates of vocational conflict were observed compared to segmentation by age. Older individuals presented a higher level of vocational alignments. In conclusion, the proposal for a Professional Guidance Plan, based on the Holland Model, is aimed at third-year high school students in the city of Loja. Keywords: Vocational orientation, vocational preferences, vocational skills, capabilities, vocational Holland Model.